Intellectual capital efficiency of listed SMEs in Malaysia / Hapsah S.Mohammad - S.Mohammad, Hapsah (Universiti Teknologi MARA, Kedah, 2021)
This study exam ines the valuead ded of intellectual capital of Malaysian listed SMEs. The data is based on the annual reports of 26 SMEs listed in the LEAP market of Bursa Malaysia from 2017 to 2019, which provides 78 observations for the analysis. The efficiency in terms of value-added is measured using modified value-added intellectual coefficient (MVAIC) model. The model is made up of human capital efficiency (HCE), structural capital efficiency (SCE), relational capital efficiency (RCE) and capital employed efficiency (CEE), the sum of these four is called MVAIC. Since the model is based on the assumption that both, physical capital and intellectual capital are a function of production, HCE, SCE and RCE represent value-added of intellectual capital, meanwhile CEE represents value-added of physical capital. The findings of the analysis reveal that the average valueadded of HCE, SCE, RCE and CEE are 2.1911, 0.5103, 0.0975 and 0.2501 respectively and MVAIC is 3.0490. The proportion between intellectual capital and physical capital is 2.7989 to 0.2501, suggesting the value-added from intellectual capital is higher in comparison to physical capital. SMEs may use the input to increase recognition of intellectual capital and address the factors affe cting intellectual capital performance in order to maximize value creation capability. The study does not consider other component of intellectual capital such as innovation capital, which becomes a limitation of the study. Future study should consider the impact of intellectual capital on SMEs performance.